Optimization of PAI Supervisors' Performance in Banyumas Regency: Strategic Steps for Strengthening Education Quality - Dudiyono, Dudiyono (The Future of Education Journal, 2024)
Islamic Religious Education (PAI) Supervisors play a strategic role in enhancing the quality of education by ensuring the effective implementation of the curriculum, providing continuous teacher development, and creating high-quality learning experiences. Through supervision that focuses on improving teacher competencies, PAI supervisors help create a learning process that is relevant and meaningful for students. This study uses a qualitative method with a descriptive approach. The findings of this study indicate that PAI supervisors in Banyumas Regency are figures who embody courage, excellence, dedication, usefulness, and a solution-oriented attitude in carrying out their duties. They are brave in facing educational challenges with innovative approaches, excel in providing solutions, and make significant contributions to improving the quality of PAI teaching in schools. With high dedication, these supervisors support and guide teachers to effectively, relevantly, and inclusively convey religious values to students. Their usefulness is reflected in the improvement of teacher competencies, the enhancement of the learning process, and the creation of a positive educational environment. Their solution-oriented attitude helps teachers overcome various technical and pedagogical challenges, making PAI supervisors in Banyumas exemplary figures in advancing religious education to build a generation that is faithful, intelligent, and virtuous.